2020
DOI: 10.1186/s13756-020-00773-y
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome signatures of nursing home residents carrying Enterobacteria producing extended-spectrum β-lactamases

Abstract: Background: The prevalence of extended beta-lactamase producing Enterobacteriaceae (ESBL-E) has been constantly increasing over the last few decades. These microorganisms that have acquired broad antibiotic resistance are now common human pathogens. Changes in the gut microbiome, induced by antibiotics or other drugs, enable expansion of these microorganisms, but the mechanisms are not yet fully understood. Objectives: The main objective was to identify specific bacteria and functional pathways and genes chara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
(43 reference statements)
4
5
0
Order By: Relevance
“…Alpha and beta diversity analysis suggests that ESBL-E carriage was not associated with substantially different gut microbiome composition or diversity, consistent with the results of other studies (68, 69). However, pairwise analysis identified multiple taxa with significantly different abundance in carriers and non-carriers.…”
Section: Discussionsupporting
confidence: 90%
“…Alpha and beta diversity analysis suggests that ESBL-E carriage was not associated with substantially different gut microbiome composition or diversity, consistent with the results of other studies (68, 69). However, pairwise analysis identified multiple taxa with significantly different abundance in carriers and non-carriers.…”
Section: Discussionsupporting
confidence: 90%
“…and Bacteroidales spp. were more abundant in the ESBL-PE carrier group and, therefore, could be considered as a potential marker for ESBL-PE carriers, as was suggested previously [12,16]. Lysinibacillus, Ruminococcaceae and Treponema were more abundant in the noncarrier group and may also serve as potential markers.…”
Section: Discussionsupporting
confidence: 67%
“…In a more recent study from Thailand, where ESBL-PE colonization is high, the most notable difference was that the phylum Bacteroidetes was more abundant in ESBL-PE noncarriers [ 15 ]. In a study carried out in France, taxonomic and functional differences were also observed between the microbiome of ESBL-PE carriers versus noncarriers, including lower diversity in ESBL carriers than noncarriers [ 16 ]. Intestinal colonization is recognized as a key risk factor regarding ESBL-PE dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…The same comparison in the Amerindian Wayampi community showed that ESBL-E faecal carriers had a lower gut bacteriobiota α-diversity than non-carriers while taxa belonging to the genera Desulfovibrio and Oscillospira (Ruminococcaceae) were associated with the absence of ESBL-E faecal carriage and Prevotella was associated with ESBL-E faecal carriage [ 19 ]. Comparison of gut bacteriobiota between ESBL-E faecal carriers and non-carriers, not in the community but in nursing home residents, found a decreased α-diversity in ESBL-E faecal carriers with a depletion in butyrate-producing bacterial species and an enrichment in succinate-producing bacterial species [ 20 ]. While the impact of microbiota on MDRO is mediated by indirect mechanisms including local and systemic immune activation and by direct mechanisms including competition for nutrients between species composing the microbiota and direct toxicity, none of these studies took ESBL-E bacterial species into account.…”
Section: Discussionmentioning
confidence: 99%